Bile acids associate with specific gut microbiota, low‐level alcohol consumption and liver fibrosis in patients with non‐alcoholic fatty liver disease. (24th April 2020) - Adams, Leon A.; Wang, Zhengyi; Liddle, Chris; Melton, Phillip E.; Ariff, Amir; Chandraratna, Harsha; Tan, Jeremy; Ching, Helena; Coulter, Sally; de Boer, Bastiaan; Christophersen, Claus T.; O'Sullivan, Therese A.; et al.
Abstract: Background: Bile acids (BAs) are synthesized by the liver and modified by gut bacteria, and may play an intermediary role between the gut microbiome and liver in promoting fibrosis in non‐alcoholic fatty liver disease (NAFLD). We investigated the associations between serum and faecal BAs, gut microbiome and fibrosis in patients with and without NAFLD and examined the impact of diet and alcohol consumption on these relationships. Methods: Adult patients (n = 122) underwent liver biopsy and BAs characterization by high‐performance liquid chromatography/mass spectrometry. Gut microbiome composition was analysed using next‐generation 16S rRNA sequencing. Diet and alcohol intake were determined by 3‐day food diary. Results: Serum and faecal BA concentrations increased progressively among non‐NAFLD controls (n = 55), NAFLD patients with no/mild fibrosis (F0‐2, n = 58) and NAFLD with advanced fibrosis (F3/4, n = 9). Progressive increases in serum BAs were driven by primary conjugated BAs including glycocholic acid [GCA] and secondary conjugated BAs. In contrast, faecal BA increase was driven by secondary unconjugated BAs (predominately deoxycholic acid [DCA]). Serum GCA levels and faecal DCA levels correlated with the abundance of Bacteroidaceae and Lachnospiraceae, and stool secondary BAs with an unclassifiable family of the order Bacteroidales ( Bacteroidales;other ). These bacterial taxa were also associated with advanced fibrosis. Modest alcohol consumption was positively correlated with faecal DCA levels and relative abundance of Lachnospiracaea and Bacteroidales;other . Conclusions: Higher serum and faecal BA levels are associated with advanced fibrosis in NAFLD. Specific gut bacteria link alterations in BA profiles and advanced fibrosis, and may be influenced by low‐level alcohol consumption.